Mobility models towards the performance of geographical-based route maintenance strategy in DSR - Sjaugi, Muhammad Farhan; Othman, Mohamed; A. Rasid, Mohd Fadlee (IEEE, 2008)
In the future, Mobile Ad hoc Networks (MANET)s are expected to be deployed in myriads of scenarios having complex node mobility and connectivity dynamics. Unfortunately, these complex movement scenarios give a tough challenge to the MANET routing protocol. We reviewed some mobility models that have different mobility characteristic, and also studied the effect of these mobility models towards the performance of geographical-based route maintenance strategy in the Dynamic Source Routing (DSR) protocol.